A facile photochemical strategy for the synthesis of high-performance amorphous MoS2 nanoparticles. Issue 10 (13th April 2021) - Sun, Haifeng; Yang, Manlin; Pu, Shan; Gou, Lichen; Lv, Caizhi; He, Juan; Hou, Xiandeng; Xu, Kailai
Abstract : A new and facile photochemical strategy for the synthesis of a high-performance amorphous MoS2 nanomaterial can be achieved by irradiating a mixed solution of ammonium molybdate, formic acid and sodium sulfide simply with a Xe lamp for 3 min. Abstract : It is difficult to avoid the formation of polysulfides by traditional chemical methods, and the synthesis of high purity amorphous MoS2 nanomaterials under ambient conditions is still a challenging task. Here we present a new and facile photochemical strategy for the synthesis of amorphous MoS2 nanomaterials, which is achieved by irradiating a mixed solution containing ammonium molybdate, formic acid and sodium sulfide simply with a Xe lamp for 3 min. The mechanism study reveals that the key step in this synthesis is the photolysis of formic acid to produce free radicals which can rapidly reduce Mo 6+ to Mo 4+, which then combines with S 2− to form MoS2 and inhibits the formation of S–S 2− by preventing S 2− from participating in the reduction reaction. In addition, the results of a series of experiments indicate that the as-prepared amorphous MoS2 features a small particle size, uniform morphology and relatively large specific surface area, and shows excellent performance in the removal of inorganic heavy metal ions (mercury, lead and cadmium ions) and organic pollutants (rhodamine B and tetracycline), catalase catalysis and a lithium battery anode, showing its great potential and broad application prospects in the fields of environmental remediation, clean energy and green catalysis.